Stress Induces Contextual Blindness in Lotteries and Coordination Games - Brocas, Isabelle; Carrillo, Juan D.; Kendall, Ryan (Frontiers in Behavioral Neuroscience, 2017)
In this paper, we study how stress affects risk taking in three tasks: individual lotteries, Stag Hunt (coordination) games and Hawk-Dove (anti-coordination) games. Both control and stressed subjects take more risks in all three tasks when the value of the safe option is decreased and in lotteries when the expected gain is increased. Also, subjects take longer to take decisions when stakes are high, when the safe option is less attractive and in the conceptually more difficult Hawk-Dove game. Stress (weakly) increases reaction times in those cases. Finally, our main result is that the behavior of stressed subjects in lotteries, Stag Hunt and Hawk-Dove are all highly predictive of each other (p-value <0.001 for all three pairwise correlations). Such strong relationship is not present in our control group. Our results illustrate a "contextual blindness" caused by stress. The mathematical and behavioral tensions of Stag Hunt and Hawk-Dove games are axiomatically different, and we should expect different behavior across these games, and also with respect to the individual task. A possible explanation for the highly significant connection across tasks in the stress condition is that stressed subjects habitually rely on one mechanism to make a decision in all contexts whereas unstressed subjects utilize a more cognitively flexible approach.